AMONG THE YOUTH: MYKHAILO HRUSHEVSKY AND THE STUDENT BODY OF LVIV UNIVERSITY - TELVAK, Vitalii; PETRECHKO, Oleh (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to determine the nature of Mykhailo Hrushevsky’s relationship with the students of Lviv University. The methodology of the research is based on an interdisciplinary approach. There has been given special emphasis on structural functional system analysis of historiographical facts and the comparative historical method, based on the principles of objectivity and historicism. There have been also used the methods of periodization, classification, and typologization. The scientific novelty of the research consists in its attempt at a comprehensive reconstruction of Mykhailo Hrushevsky’s communicative strategies in relation to the student community of Lviv University. Conclusions. Taking into consideration the summarized material, it is possible to speak of Mykhailo Hrushevsky as an innovative pedagogue in higher education. Rejecting the patriarchal practices of demonstrative professorial superiority over the student body, the scholar laid the foundation in our intellectual culture for a tradition of democratic engagement with the youth. At its core was the Enlightenment idea of the University as a harmonious community of the authoritative mentors and knowledge-seeking students. The communicative strategy chosen by M. Hrushevsky enabled the establishment of a productive, partnership-based dialogue with his students, which had several important consequences. First and foremost, the first national historiographical school emerged, whose representatives shaped the leading trends by large in the Ukrainian social sciences and humanities throughout the 20th century. The impact of bringing politically opposed student youth together behind the concept of higher education in their own mother tongue was equally important. This cultural maxim became the foundation of a long-term strategy and tactic, adopted by all Ukrainian political parties, in the struggle against discriminatory Polish policies in the region. Hrushevsky’s undisputed leadership in these initiatives made him a cult figure among the Ukrainian youth. For the same reason, his students of other nationalities, especially the Poles, often treated the scholar with a certain distance, and at times with outright hostility, echoing the rhetoric of their older peers. However, those among them not involved in political disputes and preparing for academic careers considered M. Hrushevsky to be a classic figure in Ukrainian studies and preserved a respectful memory of him. In general, it was precisely Hrushevsky’s students, who became the main participants in the complex Polish-Ukrainian dialogue during the war years and the two decades that followed. Elucidating the influence of the Professor’s ideas on the nature of this process remains a topical issue in the intellectual history of Central and Eastern Europe. Key words: M. Hrushevsky, Lviv University, students, cooperation, conflicts.